Planning and Management in Hospital Management: a scope review (Research, Society and Development, 2022)
The Unified Health System from its creation to the present day has been in a growing process of improvement and strengthening, given its importance. In order for it to be consolidated, executing the constitutional precepts more easily, it is necessary that the work and systematization processes become ever faster and more resolute. It was in this context that management instruments were developed, the subject of this study. With the objective of describing through the literature how the Covenanted and Integrated Programming, as a planning and management tool, can contribute to the improvement of Hospital Management. The Scope Review presented as a result that of the eleven articles analyzed, four were qualitative, six were retrospective and descriptive, and only one was cross-sectional descriptive. It is concluded that despite the PPI expressing the agreement between managers, ensuring universal access and comprehensiveness of health care; the level of regionalization in is insufficient, with low rates of resolvability in hospital care, in addition to the weakness in the process of cooperation between managers.